2007
DOI: 10.1038/sj.gt.3302974
|View full text |Cite
|
Sign up to set email alerts
|

Control of human mesothelin-expressing tumors by DNA vaccines

Abstract: Mesothelin has been implicated as a potential ideal target antigen for the development of antigen-specific cancer immunotherapy for the control of mesothelin-expressing cancers such as ovarian cancer, mesothelioma and pancreatic adenocarcinoma. In the current study, we utilized a DNA vaccine encoding human mesothelin (pcDNA3-Hmeso) to treat C57BL/6 mice challenged with luciferase-expressing, Hmeso-expressing ovarian cancer cell line, Defb29 Vegf-luc/ Hmeso. The therapeutic effect of the tumor-challenged mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
5
35
0
Order By: Relevance
“…Although the biological functions of mesothelin remain largely unknown, restricted distributions of mesothelin in normal tissues and its overexpression in many tumors render it an interesting therapeutic target [12,[25][26][27][28]. In recent years, expression of mesothelin and its relationship between survival outcomes has been investigated in various tumor types [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological functions of mesothelin remain largely unknown, restricted distributions of mesothelin in normal tissues and its overexpression in many tumors render it an interesting therapeutic target [12,[25][26][27][28]. In recent years, expression of mesothelin and its relationship between survival outcomes has been investigated in various tumor types [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Although the biological functions of mesothelin including enhancing chemotherapy resistance and inducing tumor invasion have been established, 24,26 studies targeting mesothelin as an ovarian cancer antigen are lacking. Several clinical trials on mesothelin target therapies are ongoing, most of which are focused on antibody or adaptive T-cell transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early evidence suggests that FDG-PET may have a useful role in evaluating MPM response to therapy. In one study [35,36], evidence of response was reported as early as after one cycle of chemotherapy by quantitative semi-automated volumebased FDG-PET analysis performed to obtain the TGV of tumor (Table 1).…”
Section: Response To Chemotherapy/radiationmentioning
confidence: 99%